Tailoring the morphology and surface plasmon coupling of BiVO4 toward efficient visible-light degradation of antibiotic pollutants - Thinh B. Le; Van M. Dinh; Phuong T.M. Ha; Dat H. Nguyen; Thien P. Nguyen; Nhi T. Y Nguyen; Tuan A. Nguyen; YB.N. Tran; Kim-Ngan N. Phan; Hiep Q. Ha; Dai-Viet N. Vo (Environmental Research, 2026)

An undescribed alkaloid from Crinum latifolium L.: structural elucidation and evaluation of its biological activity - Tuan Anh Hoang Le; Ngo Van Hieu; Nguyen Tien Dat; Vu Thi Trang; Pham Van Cong; Do Thanh Tuan; Vinh Le Ba; Lo Van Xanh; Tran My Linh; Pham Thi Hoe; Le Quynh Lien (Natural Product Research, 2026)

Phytochemical investigation of Vernonia amygdalina Delile - Pham Thi Bich Dao; Le Ba Vinh; Nguyen Tien Dat; Ngo Van Hieu; Chu Van Tan; Pham Van Cong; Nguyen Thi Thanh; Nguyen Hai Dang; Hoang Le Tuan Anh (Biochemical Systematics and Ecology, 2026)

Status and Community Structure of Coral Reefs in the Southern Vietnam - Minh-Quang Thai; Van-Long Nguyen; Xuan-Dat Mai; Xuan-Ben Hoang; Si-Tuan Vo (Ocean Science Journal, 2026)

Triterpenoids from leaves of Paramignya trimera with their alpha-glucosidase inhibition: in vitro and in silico aspects - Ngoc.-Hong Nguyen; Thuc-Huy Duong; Jirapast Sichaem; Tuan-Dat Nguyen; Gia-Huy Duong; Nguyen Thi-Phuong; Thi-My-Duyen Ngo; Thi-Cam-Tu Tran; Huy Truong Nguyen (Natural Product Research, 2026)

Pan-cancer multi-omics characterization of CDK12 and virtual screening of Vietnamese natural products for novel inhibitors - Thanh Dat Pham; Le Bao Xuyen Nguyen; Trung Duc Luu; Minh Tuan Nguyen; Nhung Thi Hong Le; Thach Phan Van (Molecular Diversity, 2026)

Phytochemical investigation of Crinum asiaticum L.: isolation and characterisation of a new dimeric alkaloid and evaluation of acetylcholinesterase inhibition with molecular docking - Le Quynh Lien; Le Ba Vinh; Vu Thi Trang; Ngo Viet Duc; Nguyen Viet Phong; Seo Young Yang; Nguyen Minh Trang; Ngo Van Hieu; Do Thanh Tuan; Nguyen Tien Dat; Tran My Linh; Pham Thi Hoe; et al. (Natural Product Research, 2025)

Diosgenin glycosides from Paris vietnamensis (Takht) H.Li with cytotoxic and inhibitory NO production activities - Le Tuan Anh Hoang; Van Cong Pham; Viet Duc Ngo; Van Hieu Ngo; Van Manh Nong; Ha Phuong Lai; Thanh Tuan Do; Tien Dat Nguyen; Ngoc Tung Nguyen (Natural Product Research, 2025)

Inhibitory nitric oxide production and cytotoxic activities of phenolic compounds from Gnetum montanum Markgr - Hieu Ngo Van; Cong Pham Van; Trang Vu Thi; Duc Ngo Viet; Tai Bui Huu; Dat Nguyen Tien; Minh Bui Quang; Anh Le Tuan; Tinh Phung Thi; Dan Nguyen Van; Hoan Vu Xuan; Anh Hoang Le Tuan (Natural Product Research, 2025)

Chemical constituents from symplocos sumuntia and their anti-inflammatory effect - Tran Thu Huong; Nguyen Van Thong; Tran Anh Quang; Le Huyen Tram; Le Thi Thuy; Nguyen Thi Thuy My; Nguyen Tuan Anh; Nguyen Tuan Hiep; Nguyen Ngoc Linh; Duc-Dat Le; Tran Thu Ha; Bui Van Thanh (Natural Product Research, 2025)

How does bias correction impact simulated drought characteristics by Regional Climate Models? - Phuong Nguyen-Ngoc-Bich; Manh-Hung Le; Tan Phan-Van; Thanh Ngo-Duc; Tuan Tran-Bui-Anh; Long Trinh-Tuan; Huong Ngo-Thi-Thanh; Dat Pham-Tien; Fredolin T. Tangang; Liew Juneng; Faye Cruz; Jing Xiang Chung; et al. (Climatic Change, 2025)

Dioxins and Related Compounds in Sediment and Soil from Craft Villages and Industrial Areas in Northern Vietnam - Xuyen Thi Nguyen; Binh Dinh Chu; Hang Thi Hong Mai; Phuc Anh Nguyen; Tra Thi Thu Nguyen; Dat Tien Nguyen; Minh Quang Bui; Tuan Anh Le Hoang; Minh Binh Tu; Nam Duc Vu (Bulletin of Environmental Contamination and Toxicology, 2025)

Tecomastane, a new megastigmane from the flowers of Tecoma stans - Thi-Hoai-Thu Nguyen; Hoang-Long To; Tuan-Dat Nguyen; Thi-Bao-Tran Nguyen; Nguyen-Kim-Tuyen Pham; Huy Truong Nguyen; Chuong Hoang Nguyen; Huu-Hung Nguyen; Ngoc-Hong Nguyen; Thuc-Huy Duong (Natural Product Research, 2023)

Microwave-assisted polyol liquefication from bamboo for bio-polyurethane foams fabrication - Tuan An Nguyen; Tuyet Minh Nguyen Ha; Binh T. Nguyen; Dat Ha; Tuan Vu Vo; Dang Mao Nguyen; Dang Khoa Vo; Ngoc Thuy Nguyen; Tuong Vy Nguyen; DongQuy Hoang (Journal of Environmental Chemical Engineering, 2023)

A new steroidal saponin from the aerial parts of Solanum torvum - Le Canh Viet Cuong; Nguyen Phuc Khanh Nhi; Tran Phuong Ha; Le Tuan Anh; Ton That Huu Dat; Phung Thi Thuy Oanh; Nguyen Thi Minh Phuong; Vo Thi Kim Thu; Ho Viet Duc; Hoang Le Tuan Anh (Natural Product Research, 2022)

Research and Development Prospects for Sugarcane Industry in Vietnam - Thi-Thao Nguyen; Quoc-Tuan Hoang; Tien-Thanh Nguyen; Tuan-Anh Pham; Anh-Duong Cao; Hong-Duong Pham; Viet-Hung Le; Thu-Trang Vu; Ngoc-Hung Pham; Tien-Cuong Nguyen; Kim-Anh To; Van-Hung Nguyen; et al. (Sugar Tech, 2022)

Secondary metabolites from Valeriana jatamansi with their anti-inflammatory activity - Le Huyen Tram; Nguyen Van Thong; Le Thi Thuy; Nguyen Tuan Anh; Nguyen Hoang Minh; Tran Thi Minh; Nguyen Thi Hong Phuong; Tran Thu Ha; Thi Minh Nguyet Nguyen; Duc Dat Le; Nguyen Dinh Hiep; Jong-Tae Park; et al. (Natural Product Research, 2022)

A new triterpenoid from the stems of Kadsura coccinea with antiproliferative activity - Le Huyen Tram; Tran Thu Huong; Le Thi Thuy; Nguyen Van Thong; Nguyen Tuan Anh; Nguyen Hoang Minh; Tran Thu Ha; Dao Anh Dung; Nguyen Phuong Thao; Phuong Thien Thuong; Duc Dat Le; Nguyen Dinh Hiep; et al. (Natural Product Research, 2022)

Cytotoxic activity of steroidal glycosides from the aerial parts of Solanum torvum collected in Thua Thien Hue, Vietnam - Le Canh Viet Cuong; Le Thi Lien; Nguyen Thi Minh Phuong; Vo Thi Kim Thu; Tran Phuong Ha; Ton That Huu Dat; Pham Thi Hai Ha; Tran Thi Phuong Anh; Hoang Le Tuan Anh (Natural Product Research, 2021)

Stercufoetin A, new oleanane-type triterpenoid from the leaves of Sterculia foetida L. - Nguyen Kim Tuyen Pham; Trung Duan Nguyen; Tran Duy Cuong Doan; Tuan Dat Ha; Nguyen Minh An Tran; Trong Duc Tran; Dinh Tri Mai; Tan Phat Nguyen (Natural Product Research, 2021)

Taro Colocasia esculenta as an alternative host plant for rearing cassava mealybug (Hemiptera: Pseudococcidae) and its parasitoid Anagyrus lopezi (Hymenoptera: Encyrtidae) - Dat Nguyen Tuan; Layheng Sam; Chi Zhang; Chau Nguyen Ngoc Bao; Shun-ichiro Takano; Keiji Takasu (Applied Entomology and Zoology, 2020)

Genetic analysis of 55 northern Vietnamese patients with Wilson disease: seven novel mutations in ATP7B - Le Anh Tuan Pham; Trong Tue Nguyen; Hoang Bich Nga Le; Dat Quoc Tran; Cam Tu Ho; Thinh Huy Tran; Van Thanh Ta; The Hung Bui; Van Khanh Tran (Journal of Genetics, 2017)

A new megastigmane sulphoglycoside and polyphenolic constituents from pericarps of Garcinia mangostana - Thu Huong Tran; Tram Le Huyen; Thi Minh Tran; Tuan Anh Nguyen; Thanh Binh Pham; Dat Nguyen Tien (Natural Product Research, 2016)

Bioeconomics of mud crab, Scylla paramamosain , culture in Vietnam - Elizabeth H. Petersen; Truong H. Phuong; Nguyen Van Dung; Pham T. Giang; Nguyen K. Dat; Vu A. Tuan; Tran V. Nghi; Brett D. Glencross (Reviews in Aquaculture, 2013)
The results of bioeconomic analysis informed by a survey of 80 small‐scale mud crab farmers in Vietnam are presented in this paper. Mud crab farming in Vietnam is profitable, with net revenue being approximately 135 and 41 million VND/year (USD 7000–USD 2100 per year) in the central and southern regions, respectively. Profitability was significantly higher in the centre compared with the north, as almost three times the biomass is harvested in the centre compared with the south (in turn, due to higher aquaculture area and survival rates). The benefit–cost ratio (the ratio between total revenue and total costs) is 3.55 in the centre and 1.97 in the south. The crabs are fed almost exclusively on low‐value finfish in the centre and the south. Feeding rates were found to be low, with 95% of biomass gain coming from natural feed in the environment rather than supplementary feeding by the farmer. If pellets are to be adopted widely by mud crab farmers, negative perceptions regarding the poor adaptability of mud crab to pellets (northern farmers only), relatively slow growth rates compared with low‐value finfish and lack of availability of pellets need to be overcome.